Eksploitasi Anak sebagai Dampak Kemiskinan dalam Novel Kita Pergi Hari Ini Karya Ziggy Zezsyazeoviennazabrizkie (Kajian Sosiologi Sastra) - Stella Lasverina Limparu; Khothibul Umam; Yuniardi Fadilah (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to describe the structure and explain the issue of child exploitation as a consequence of poverty in the novel Kita Pergi Hari Ini (KPHI) using a literary sociology approach, along with the theories of fiction structure and child exploitation. Data were collected through literature study and note-taking techniques, and analyzed using data reduction, data presentation, and verification. The findings reveal that the main theme of the novel is the struggle of children to obtain a better life amidst poverty and exploitation. The main characters consist of five children and a recruiter named Nona Gigi, with a progressive plot driving the narrative. Poverty is portrayed through economic hardship and limited access to employment due to a system dominated by certain groups, leading parents to relinquish their responsibilities and hand over their children to exploitative parties. The forms of exploitation depicted in the novel include emotional, verbal, and physical abuse, with emotional abuse being the most dominant. The novel offers social criticism of a system that fails to protect children and emphasizes the importance of child protection and poverty alleviation to prevent further exploitation.Keywords: Kita Pergi Hari Ini, Child Exploitation, Poverty